Biomechanical analysis of PDMS channels using different hyperelastic constitutive models - Cardoso, Cátia (2015)
Brain aneurysms are pathological dilatations of cerebral arteries and are known as one of the most common and serious cerebrovascular events. Most cerebral aneurysms do not cause symptoms until they become large, beginning to break up. This study's main objective is the numerical characterization of biomechanical behavior of aneurysms, taking into ac-count different geometric and physiological parameters, in order to analyze the blood vessel wall behavior during the formation of an aneurysm in order to understand what leads to its formation and where are most conducive to its rupture zones. Simulation of the Newtonian fluid flow (glycerin, with well-known properties and sufficient viscosity to measure the pressure drops) was performed using the commercial finite method package Ansys® - Fluent, and pressure along the channel was determined. These pressures were imported into the channel, in the Ansys®- Static Structural, in order to be able to evaluate and analyse the deformations and stresses in the channel wall, caused by internal pressure induced by the fluid flow. To do this, the most known hyper-elastic constitutive models were used. and it was concluded that any constitutive model can be applied to this kind of studies, allowing to visualize where pressure achieve maximums and consequently, the most favorable areas to the rupture.